Sphyrna tudes, Smalleye Hammerhead - Pollom, R. (2020)
The Smalleye Hammerhead (Sphyrna tudes) is a medium-sized (to 150 cm total length) shark that occurs in the Western Central and Southwest Atlantic from Colombia to the Rio de La Plata, Argentina. It inhabits inshore waters over the continental shelf at depths of 5–80 m. It is captured in intense and largely unmanaged commercial and artisanal beach seines, gillnets, longlines, and trawls throughout its geographic range. This shark is targeted or retained as bycatch for its meat, which is consumed or sold locally. There are few data on population reduction but these intensive unmanaged fisheries are suspected to have caused reductions and possibly local extinctions throughout this species' range. For example, in Brazil, this hammerhead has not been recorded in 35 years from Ceará state and it is considered by local fishers to be depleted in Bahia state. This shark is supposed to be strictly protected in Brazil, but it is clear that it is still landed and traded in various states. Overall, due to intense and largely unmanaged fisheries across its range, lack of refuge at depth, suspected declines in many areas and local extinctions suspected from an absence of records (despite continued sampling and observation), and its relatively unproductive life history, it is suspected that the Smalleye Hammerhead has undergone a population reduction of >80% over the past three generations (37 years), and it is assessed as Critically Endangered A2bd.